2002
DOI: 10.1046/j.1365-2109.2002.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased stocking density influences the acute physiological stress response of common carpCyprinus carpio(L.)

Abstract: The physiological response of common carp, Cyprinus carpio (L.) to increased stocking density and an additional acute net confinement stressor was investigated. Stocking densities were increased from 28.4 to 56.8 or 113.6 kg m À3 by the use of crowding screens and fish were sampled from the crowded groups after 15, 39 and 87 hours of crowding (hc). A transient elevation of plasma cortisol was found in the higher density group after 15 hc before values returned to control levels. Increased stocking density also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
67
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 30 publications
18
67
2
1
Order By: Relevance
“…Resting plasma glucose and lactate concentrations did not differ between transgenic and non-transgenic carp, and values were comparable to those from other studies on carp (Pottinger, 1998;Ruane et al, 2001Ruane et al, , 2002. Both groups exhibited a typical secondary metabolic stress response to exhaustive exercise, as indicated by elevated plasma glucose and lactate concentrations (Barton, 2002;Iwama et al, 2004;Portz et al, 2006), but transgenic fish appeared to clear lactate more quickly than controls.…”
Section: Physiological Response To Exhaustive Exercisesupporting
confidence: 73%
See 1 more Smart Citation
“…Resting plasma glucose and lactate concentrations did not differ between transgenic and non-transgenic carp, and values were comparable to those from other studies on carp (Pottinger, 1998;Ruane et al, 2001Ruane et al, , 2002. Both groups exhibited a typical secondary metabolic stress response to exhaustive exercise, as indicated by elevated plasma glucose and lactate concentrations (Barton, 2002;Iwama et al, 2004;Portz et al, 2006), but transgenic fish appeared to clear lactate more quickly than controls.…”
Section: Physiological Response To Exhaustive Exercisesupporting
confidence: 73%
“…Several studies have reported that crowding (Yin et al, 1995;Ruane et al, 2002) or infection by pathogens (Harikrishnan et al, 2003) reduce total plasma protein concentrations in carp. Significant changes in the amounts and activities of the serum proteins in fish during stress suggest that stressed fish may have decreased disease resistance and become more susceptible to infection (Yin et al, 1995).…”
Section: Physiological Response To Exhaustive Exercisementioning
confidence: 99%
“…However, quantifying stressful conditions proved difficult with many authors reporting a transient increase in plasma cortisol levels during stress, e.g. during crowding (Tort et al, 1996;Ruane et al, 2002) while others reported no effect (Procarione et al, 1999) or reduced cortisol levels (Leatherland and Cho, 1985).In this study, the plasma cortisol level in fish increased slightly during transport (from 258.57 ng per ml in Hluboká to 301.94 ng/ml in Boheľov), but the increase was not significant. At the beginning of the experiment, carp responded to netting and catching during pre-transport manipulation with a mild cortisol response, similarly to results reported by Ruane et al (2002).…”
mentioning
confidence: 61%
“…However, quantifying stressful conditions proved difficult with many authors reporting a transient increase in plasma cortisol levels during stress, e.g. during crowding (Tort et al, 1996;Ruane et al, 2002) while others reported no effect (Procarione et al, 1999) or reduced cortisol levels (Leatherland and Cho, 1985).…”
mentioning
confidence: 99%
“…Many researchers reporting transient elevation of cortisol levels during crowding stress (Barcellos et al 1999;Ruane et al 2002), while others report no effect (Da Rocha et al 2004;Fanouraki et al 2007;Vijayan and Leatherland 1990) or even a reduction (Leatherland and Cho 1985).…”
Section: Discussionmentioning
confidence: 99%